2018
DOI: 10.1007/s13679-018-0312-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Excessive Gestational Weight Gain and Postpartum Weight Retention

Abstract: Recent findings demonstrate that tailored nutrition counseling and adapting certain eating patterns, supervised exercise programs aiming at achieving at least moderate level of physical activity, and interactive and monitored behavior change interventions are effective in reducing excessive GWG and PPWR. Among the pharmacologic agents, Metformin has been shown to reduce GWG. Excessive GWG and PPWR are associated with adverse maternal and neonatal outcomes. Recent evidence shows that weight during gestation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 45 publications
1
15
0
3
Order By: Relevance
“…Adequacy of GWG in diff erent groups according to their pre prgnancy BMI classifi cation (Above, within and below the recommended GWG range) conclusive pregnancy interventions for preventing GWG (17). After that, studies showed the effectiveness of exercise and diet interventions alone and in combination for preventing GWG (18,19,20). Our results showed similar findings, as both the exercise group and the diet group were effective in preventing excess GWG in pregnant Indian women.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Adequacy of GWG in diff erent groups according to their pre prgnancy BMI classifi cation (Above, within and below the recommended GWG range) conclusive pregnancy interventions for preventing GWG (17). After that, studies showed the effectiveness of exercise and diet interventions alone and in combination for preventing GWG (18,19,20). Our results showed similar findings, as both the exercise group and the diet group were effective in preventing excess GWG in pregnant Indian women.…”
Section: Discussionsupporting
confidence: 75%
“…D i HE grupa su imale najviše ispitanica koje su imale GTR u okviru preporučenog opsega, dok su grupe SE i SED imale najviše ispitanica sa GTR-om ispod preporučenog opsega. Ipak, ovi rezultati nisu uticali na telesnu težinu novorođenčeta ni u jednoj grupi (18,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)9 kg/m2), pri čemu je D grupa imala najefektnije održavanje GT sa 15%, 55% i 30% žena koje dobijaju na težini, ne dobijaju i gube na težini, respektivno. U SE i SED grupama najviše žena je imalo najnižu stopu održavanja telesne težine 2 meseca nakon porođaja, a zatim u grupama HM, D i C; tj., rezultati pokazuju očekivani trend kliničke promene iako razlike nisu bile statističke značajne (p=0,12).…”
Section: Sažetakunclassified
“…[8][9][10][11][12][13] Studies have also shown that postpartum behavioural weight loss interventions after delivery can help women reduce postpartum weight retention (PPWR) and risk for future obesity. [14][15][16][17] Because adults face multiple demands on their time, remote delivery (i.e. phone) of behavioural counselling and integration of such counselling within the prenatal care setting where women receive usual care has the potential to enhance patient engagement and satisfaction and to promote dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…Strong and increasing evidence supports behavioural interventions to limit GWG and improve health behaviours 8–13 . Studies have also shown that postpartum behavioural weight loss interventions after delivery can help women reduce postpartum weight retention (PPWR) and risk for future obesity 14–17 . Because adults face multiple demands on their time, remote delivery (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed strategies to prevent excessive gestational weight gain; these strategies include individualized nutrition program, focused and supervised prenatal exercise with proper intensity and duration measures, and goal-targeted behavior modifications. 10 11 These interventions reportedly work best to prevent excessive gestational weight gain when performed simultaneously and should be routinely discussed during prenatal visits. Weight gain in pregnancy is potentially modifiable, and therefore, may be leveraged to improve maternal outcomes.…”
Section: Commentmentioning
confidence: 99%